Study of photodynamic, sonodynamic and antioxidative influence on HeLa cell line - Tománková, Kateřina; Kolářová, Hana; Vachutka, Jaromír; Zapletalová, Jana; Hanáková, Adéla; Kaplová, Eva (Indian Journal of Biochemistry & Biophysics, 2014)
Photodynamic treatment (PDT) in combination with sonodynamic treatment (SDT) can be used as suitable methods to treat malignant and benign diseases or combat resistant bacteria. Both methods affect the production of reactive oxygen species (ROS). On the other hand, antioxidants are useful for cell protection against ROS. This work was aimed to study the effect of PDT and SDT treatments on the HeLa cell line using antioxidant Pronalen Sensitive Skin as a protection from free radicals in the cells. We evaluated the effect of sensitizer ClAlPcS2 using battery of in vitro methods, including MTT assay, kinetic production of ROS, mitochondrial membrane potential change, type of cell death and microscopic analysis. Ultrasound treatment was observed to increase the production of ROS, only in combination with PDT, particularly at higher concentrations of ClAlPcS2. The added antioxidant acts as protection against free radicals and has potential as a dietary supplement against aging or free radicals. The results of study suggested that ClAlPcS2 could be used as a potential photosensitizer for treatment of a specific type of cancers.
Keywords: HeLa Cells; apoptóza; Antioxidants; Ultrasonic Therapy; Membrane Potential, Mitochondrial; Apoptosis; lidé; HeLa buňky; Photochemotherapy; nekróza; Reactive Oxygen Species; Photosensitizing Agents; ultrazvuková terapie; fotosenzibilizující látky; Necrosis; membránový potenciál mitochondrií; antioxidancia; reaktivní formy kyslíku; fotochemoterapie; Humans